The quest for relevance in teacher education paradigms and paradoxes - Cortes, Josefina R. (Education quarterly.)
This paper is based on the results or research studies, views and current concerns about Philippine education articulated in recent newspaper articles, and the results of the survey of our students? and faculty memebrs? conceptions of an adequately prepared teacher, school administrator, and guidance counsellor.